LATIHAN JALAN 30 MENIT PADA PASIEN DIABETES MELLITUS - Jundapri, Kipa; Grace, Rury; Suharto, Suharto (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Uncontrolled blood sugar levels can be controlled through physical activity, such as walking, in addition to diet management. Walking is a non-pharmacological measure recommended daily for diabetes mellitus patients to lower blood sugar levels and prevent complications. The purpose of this study was to provide an overview of 30-minute walks to control blood sugar levels in patients with diabetes mellitus. This method was descriptive study with 30 respondents with diabetes mellitus. Walking exercises were carried out three times a week for 30 minutes. The results showed that 30 minutes of walking can reduce blood sugar levels in respondents, with an average random blood sugar level of 240 mg/dL then decreasing to an average of 134 mg/dL. Based on the results, it was found that respondents experienced a decrease in blood sugar levels after receiving health education about the benefits of 30-minute walks done three times a week